Synergistic Effect Analysis of Ecological Protection and Environmental Law and Ecological Civil Code - Zeng, Linyichen; Zhang, Shuo (Journal of environmental and public health, 2022)
In order to further curb the damage to the ecological environment from the perspective of legal synergistic supervision, a synergistic analysis method between the ecological protection environmental law and the ecological Civil Code is proposed. Coordinated supervision, with the new Civil Code as the research background, from the perspective of interpretation, explores the solution to the problem of “ecological environmental damage” in the newly promulgated Civil Code for behavior that damages the ecological environment. The research results believe that, from the perspective of rights, environmental rights should be regarded as the concentrated expression of rights in the sense of private law in the ecological environment law. Article 1234 of the Tort Liability Section stipulates that “the state-specified agency or the law-specified organization” as the representative of environmental public interests proposes damage. The request resolves the legitimacy of relevant agencies and organizations as civil subjects to represent environmental public interests. Finally, it clearly stipulates the responsibility for ecological restoration, expands the way of undertaking tort liability caused by environmental damage, and solves the problem that it was limited to “restoration” in the past and could not be actually performed.